PENGEMBANGAN KEMAMPUAN BERBAHASASISWATUNARUNGU:Studi Kasus Tentang Upaya Pengembanganan Kemampuan BerbahasaSiswa Tunarungu di SLB X Bandung, Tahun 2005)\ - Tonny Santosa G, - (2005)
Basic ideas ofthis thesis, was start from teacher's complaint for having communication block which was caused by students' language ability that has not reach post-linguality. So this research is focusing to look for answer for the question "How does the effort in develop language ability of students with hearing impairment at SLBX Bandung? This research is conducted to see (1) understanding of teachers about implication of hearing impairment (2) implementation of understanding related to development of language ability ( 3) activity of teacher in developing of language ability ( 4) execution of supporting factors in order to develop language ability. Result of this research is expected to be usefully for the teachers and headmaster as consideration to determine of the policy in election of communications method, instruction method and arranging development program of language ability so the teachers more readiness and have adequate ability to execute their role as itinerant teacher at the inclusive education era. This research is using qualitative approach. Strategy of research is single case study where school as a unit analysis with 6 teachers as sub-unit, consist of 2 TKLB teachers, 3 SDLB teachers, 1 SMPLB teacher and a head master. Data collecting technique is using interview and observation and analyze of data by inter-active model with reduction of data, displaying data, making conclusion and data verification. Theoretical background were focusing on language development theory with whole language approach through oral communication and teaching method based on conversation with language across the curriculum concept. Results show that teachers have comprehensive understanding of hearing impairment implication. But the implementations of these understandings are irrelevant with language development effort. Even though teachers are using oral communication method, but the school doesn't have the policy in deciding which communication and teaching method are being used. School doesn't have program to develop language ability conceptually which gives way for teachers to teach language the way they prefer. In other words, school doesn't have collective identity which reflects school with oral methods. Students language ability in general has not reach post-linguality. This research recommends headmaster to make policy by choosing oral communications method because children with hearing impairment give sign which understood by limited environment and Indonesian Sign Language System (SIBI) has not fully mastered by teachers and school community. Words in Indonesia Language are easier to read through their visime and fonemic, thus, oral communications is the natural way to communicate. The recommended teaching method is the method which reffered to reflective conversation. The headmaster have to develop a program conceptually such as training to improve teacher's knowledge in teaching method. It also needs monitoring, supervising and evaluation to see teacher's performance in their effort to develop student's language ability. Teachers were expected to open their mind to embrace innovation and using Maternal Reflective Method with all consequences. School communities were also expected to give language input to students to help them achieve post-linguality.